2019
DOI: 10.1111/cas.13982
|View full text |Cite
|
Sign up to set email alerts
|

Integrative molecular profiling identifies a novel cluster of estrogen receptor‐positive breast cancer in very young women

Abstract: Very young breast cancer patients are more common in Asian countries than Western countries and are thought to have worse prognosis than older patients. The aim of the current study was to identify molecular characteristics of young patients with estrogen receptor ( ER )‐positive breast cancer by analyzing mutations and copy number variants ( CNV ), and by applying expression profiling. The whole exome and transcriptome of 47 Korean young breast cancer ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Gene fusions were preferentially detected in high-grade disease and/or endocrine-resistant forms of ESR1 + BC [ 10 , 13 ]. Particularly, an enrichment of ESR1-CCDC170 fusion was previously reported in HER-positive patients (luminal A 9%, luminal B 3–8% and HER2 3.1%) and was correlated with a worse clinical outcome after endocrine therapy [ 9 , 15 , 16 ]. The ESR1-AKAP12 fusion was identified in 6.5% breast cancer that were resistant to letrozole aromatase inhibitor treatment [ 17 ].The novel fusion ESR1-ARMT1 was instead detected in a HER2-negative patient with luminal A-like subtype [ 16 ] and in a breast cancer patient who had not received endocrine therapy [ 18 ].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Gene fusions were preferentially detected in high-grade disease and/or endocrine-resistant forms of ESR1 + BC [ 10 , 13 ]. Particularly, an enrichment of ESR1-CCDC170 fusion was previously reported in HER-positive patients (luminal A 9%, luminal B 3–8% and HER2 3.1%) and was correlated with a worse clinical outcome after endocrine therapy [ 9 , 15 , 16 ]. The ESR1-AKAP12 fusion was identified in 6.5% breast cancer that were resistant to letrozole aromatase inhibitor treatment [ 17 ].The novel fusion ESR1-ARMT1 was instead detected in a HER2-negative patient with luminal A-like subtype [ 16 ] and in a breast cancer patient who had not received endocrine therapy [ 18 ].…”
Section: Introductionmentioning
confidence: 88%
“…Particularly, an enrichment of ESR1-CCDC170 fusion was previously reported in HER-positive patients (luminal A 9%, luminal B 3–8% and HER2 3.1%) and was correlated with a worse clinical outcome after endocrine therapy [ 9 , 15 , 16 ]. The ESR1-AKAP12 fusion was identified in 6.5% breast cancer that were resistant to letrozole aromatase inhibitor treatment [ 17 ].The novel fusion ESR1-ARMT1 was instead detected in a HER2-negative patient with luminal A-like subtype [ 16 ] and in a breast cancer patient who had not received endocrine therapy [ 18 ]. Moreover, a recently study based on molecular characterization of luminal breast cancer in African American women reported the fusions at a frequency of 11% for ESR1-CCDC170, 8% for ESR1-AKAP12 and 6% for ESR1-ARMT1 [ 19 ].…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, group B patients included 11q13 ( CCND1 ) amplification and activation of the ubiquitin-mediated proteolysis pathway. Moreover, 17q12 ( ERBB2 ) amplification and lower ER and PR expressions were observed in group C, which was also determined by immune activation and lower EMT level when compared with group B [52]. The higher incidence of basal-like cancers in very young women may be associated with an increase in the expression of BRCA1 mutations, luminal progenitors, and c-kit in younger patients [53].…”
Section: Pathological Characteristics and Tumor Behaviormentioning
confidence: 99%
“…Management of BC depends on the multi-professional cooperation, stratification of patient risk, improvement in the understanding of molecular mechanism and pathology, as well as prognostic and predictive modeling. Nevertheless, due to the heterogeneity, an assignment to mentioned subgroups is not adequate for the establishment of the newest strategies of clinical management [52].…”
Section: The Advanced Approach By Predictive Preventive and Persmentioning
confidence: 99%
“…These studies have reported changes in the expression of specific genes, gene sets, or signatures in young patients as compared with those in older patients with BC. For example, patients aged <35 years with ER-positive BC showed an upregulation of signatures pertaining to the insulin-like growth factor receptor and stromal microenvironment in luminal A BC subtype [ 20 ]. Patients aged <45 years with BC showed an increased expression of growth factors and cell cycle progression genes [ 21 ]; patients aged <45 years showed a high prevalence of the GATA3 mutation [ 22 ]; those aged <35 years showed an increased expression and/or mutations of GATA3 and ARID1A [ 23 ]; and patients aged <40 years showed an increased expression of RANKL [ 24 ].…”
Section: Introductionmentioning
confidence: 99%